Efficacy of topical povidone iodine ear drops 5% in chronic suppurative otitis media - Utomo, Bambang Suprayogi Resi; Kusumawati, Dyah Sari; Saputra, Egon Ilman; Hanny, Hervina Restianty (PERHATI-KL, 2023)
Background: Povidone Iodine (PVP-I) is a well-known antiseptic and chemical compound to kill and inhibit the growth of microorganisms. Povidone Iodine 5% antiseptics are expected to have similar or better clinical efficacy compared with topical antibiotics in Chronic Suppurate Otitis Media (CSOM) patients but this is not fully clear. Topical antibiotics can also come in the form of ear drops. Topical antibiotics are the standard in CSOM patient therapy. This study aimed to discover Povidone Iodine 5% in terms of clinical efficacy in CSOM patients. Method: This research was conducted in accordance with the Cochrane Handbook for Systematic Review and Intervention, in adherence with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses. All clinical trial studies comparing Povidone Iodine with topical antibiotics in CSOM management were performed in several databases including Google Scholar, PubMed, Springer Link, and Cochrane. The collected data from a number of samples have improved each study, seen by the clinical signs and symptoms. Results: A total of 407 research articles were included in this analysis then we had 24 works of literature. Final decision, only 2 literature met the criteria to review. Al-Abbasi et al study, PVP-I 5% recovered 13/16 (81.2%), Neomycin + Dexamethasone 11/16 (68.7%) and saline 4/16 (25%). Jaya et al study, PVP-I-5% recovered: 16/18 (88.8%), Ciprofloxacin 0.3%: 19/21 (90.4%), and no side effects were found in both studies. Conclusion: Our analysis revealed that PVP-I 5% have similar treatment as great as the efficacy of topical antibiotics, and there were no side effects of treatment. More evidence-based research is needed to determine the effectiveness of topical PVP-I 5% in the treatment of CSOM.